The Effect of Science and Technology-Based LKPD on Material and Its Changes on Student Motivation and Learning Outcomes - Siti Nur Wahyuningsih; Okta Suryani; Desy Kurniawati; Riga (Postgraduate, University of Mataram, 2026)
This study aimed to develop Science, Technology, and Society (STS)-based student worksheets (LKPD) on the topic of substances and their changes and to examine their effectiveness in improving the motivation and learning outcomes of tenth-grade students at SMKN 1 Timpeh. This development research employed the Plomp Model, which consists of Preliminary Research, Prototyping Phase, and Assessment Phase. The participants were 32 tenth-grade students, comprising 21 students in the experimental class and 11 students in the control class. The instruments included validation sheets, practicality questionnaires, a learning motivation questionnaire, and a learning outcomes test. The data were analyzed using descriptive and inferential statistics. The results indicated that the worksheets were valid, with Aiken’s V scores of 0.86 for content, 0.90 for presentation, 0.88 for language, and 0.88 for contextual aspects, with an average of 0.88. The worksheets were also very practical, with teacher and student practicality scores of 93%. In the Assessment Phase, the experimental class showed significantly higher motivation and learning outcomes than the control class (p = 0.012). Therefore, the developed worksheets are valid, practical, and effective for chemistry learning.